STUDI KOMPRESIBILITAS UDARA KETIKA BERINTERAKSI DENGAN AIR DALAM SISTEM VENTURI MANOMETER TERBUKA - Rasagama, I Gede (Universitas Tadulako, 2022)
The study purpose was to determine the change in the air density value (compressibility) when interacting with water in an open manometer venturi system. In this experimental study, the difference in water height of the manometer arms was conditioned as dependent variable, the diameter of the venturi tube and the mechanical power were conditioned as 2 independent variables where one changed the other was constant, and the density of air was conditioned as a moderate variable. The research shows: (1) the air density affects the relationship between the difference in water surface height and diameter where the value decreases as the diameter increases and the mechanical strength remains constant, the mean gradient is -6.31E-02 kg/m4 for the convergent pattern and -6.87E-02 kg /m4 for the divergent pattern, the mean of determination coefficient is 43.6% for the divergent pattern and 44.4% for the divergent pattern; 2) the air density affects the relationship between the difference in water level and the mechanical power, where the value decreases when the mechanical power increases but the diameter remains constant, the mean gradient is -5.45E-05 kg/m3W and the mean of determination coefficient is 45.9%.